Body size and substrate type modulate movement by the western Pacific crown-of-thorns starfish, Acanthaster solaris. - Morgan S Pratchett; Zara-Louise Cowan; Lauren E Nadler; Ciemon F Caballes; Andrew S Hoey; Vanessa Messmer; Cameron S Fletcher; David A Westcott; Scott D Ling (PLoS ONE, 2017)
The movement capacity of the crown-of-thorns starfishes (Acanthaster spp.) is a primary determinant of both their distribution and impact on coral assemblages. We quantified individual movement rates for the Pacific crown-of-thorns starfish (Acanthaster solaris) ranging in size from 75-480 mm total diameter, across three different substrates (sand, flat consolidated pavement, and coral rubble) on the northern Great Barrier Reef. The mean (±SE) rate of movement for smaller (<150 mm total diameter) A. solaris was 23.99 ± 1.02 cm/ min and 33.41 ± 1.49 cm/ min for individuals >350 mm total diameter. Mean (±SE) rates of movement varied with substrate type, being much higher on sand (36.53 ± 1.31 cm/ min) compared to consolidated pavement (28.04 ± 1.15 cm/ min) and slowest across coral rubble (17.25 ± 0.63 cm/ min). If average rates of movement measured here can be sustained, in combination with strong directionality, displacement distances of adult A. solaris could range from 250-520 m/ day, depending on the prevailing substrate. Sustained movement of A. solaris is, however, likely to be highly constrained by habitat heterogeneity, energetic constraints, resource availability, and diurnal patterns of activity, thereby limiting their capacity to move between reefs or habitats.